INTERPRETING THE BERSIH DESA TRADITION THROUGH HINGE EPISTEMOLOGY: HERMENEUTIC INSIGHTS FROM WITTGENSTEIN AND RICOEUR IN HISTORY EDUCATION - Khoirul Huda (Jurnal Pendidikan Sejarah Indonesia, 2026)
Local cultural traditions play a crucial role in shaping historical consciousness and communal identity, yet they remain under-theorized within formal history education. This systematic literature review examines how the Bersih Desa tradition can be meaningfully interpreted and integrated into history education through the combined lenses of Wittgenstein’s hinge epistemology and Paul Ricoeur’s hermeneutics. Drawing on interdisciplinary literature across philosophy, education, religious studies, and cultural studies, the review synthesizes findings from four thematic areas: cultural significance of tradition, hinge epistemology, hermeneutic interpretation, and interdisciplinary pedagogical integration. The analysis demonstrates that Bersih Desa functions as a communal epistemic hinge grounded in shared beliefs, practices, and values, while simultaneously operating as a dynamic cultural narrative that evolves through interpretation and social change. Integrating these philosophical frameworks enables educators to move beyond descriptive treatments of local traditions toward reflective, critical, and context-sensitive pedagogical practices. The review identifies persistent gaps in the literature, particularly regarding the alignment of Western philosophical paradigms with Southeast Asian indigenous knowledge systems, and highlights the need for empirical and collaborative research in local educational contexts. This study contributes a theoretically grounded model for incorporating local traditions into history education, promoting cultural continuity, epistemic justice, and critical historical understanding.